Seasonal changes in anthropometric and physical characteristics within English academy rugby league players - Till, K.; Jones, B.; Emmonds, S.; Tester, E.; Fahey, J.; Cooke, C. (The Journal of Strength and Conditioning Research, 2014)
Professional rugby league clubs implement training programmes for the development of anthropometric and physical characteristics within an academy programme. However, research that examines seasonal changes in these characteristics is limited. The purpose of the study was to evaluate the seasonal changes in anthropometric and physical characteristics of academy rugby league players by age category (i.e., under 14, 16, 18, 20). Data were collected on 75 players pre- and postseason over a 6-year period (resulting in a total of 195 assessments). Anthropometric (body mass, sum of 4 skinfolds) and physical (10- and 20-m sprint, vertical jump, Yo-Yo intermittent recovery test and 1 repetition maximum squat, bench press, and prone row) measures were collected. The under 14s and 16s showed greater seasonal improvements in body mass (e.g., under 14s = 7.4 ± 4.3% vs. under 20s = 1.2 ± 3.3%) and vertical jump performance than under 18s and under 20s. In contrast, under 18s and under 20s players showed greater seasonal improvements in Yo-Yo performance and 10-m sprint (e.g., under 14s = 1.3 ± 3.9% vs. under 20s = -1.9 ± 1.2%) in comparison to under 14s and under 16s. Seasonal strength improvements were greater for the under 18s compared with under 20s. This study provides comparative data for seasonal changes in anthropometric and physical characteristics within rugby league players aged 13-20 years. Coaches should be aware that seasonal improvements in speed may not exist within younger age categories, until changes in body mass stabilize and consider monitoring changes in other characteristics (e.g., momentum). Large interplayer variability suggests that player development should be considered on an individual and longitudinal basis